Concomitant Chylothorax and Chyloperitoneum with Newly Diagnosed: B-Cell Lymphoma: A Case Report - Siahaan, Sylvia Sagita; Prasetya, Ignatius Bima; Pradhana, Cindy Meidy Leony (Medicinus, 2023)
Chylothorax and Chyloperitoneum are an infrequent condition, characterized by the accumulation of chyle in the pleural and peritoneum cavity. We report an uncommon presentation of concomitant chylothorax and chyloperitoneum caused by diffuse B- cell Lymphoma. A 60-year woman was admitted with progressive shortness of breath, abdominal fullness, cough when lying down on one week duration. She also complains progressive non painful neck lump, night sweats, and weight loss. Chest radiograph showed right pleural effusion. CT scan abdomen with contrast revealed ascites with lobulated mass and multiple lymphadenopathy. Thoracocentesis and paracentesis were performed, revealed exudative with yellow and milky appearance and elevated triglyceride. Histopathologic confirmed diffuse large B-cell lymphoma. Chylothorax concomitant with chylous ascites is rarely encountered. Serous effusion occur often in malignant lymphomas. Management of chylothorax and chyloperitoneum is conservative measures and treat the aetiology. Effusion often becomes a chronic problem that persist although the lymphoma has been treated.